Psychometric evaluation of the short version of the Defense Style Questionnaire on Serbian healthy adult men - Vojvodić, Aleksandra R. (Vojnosanitetski pregled, 2021)
Background/Aim. The most famous instrument for measuring psychological mechanisms of defense is the Defense Style Questionnaire (DSQ-40), which has been increasingly used in our country. In Serbia empirical norms for male adolescent population and for elderly male adults were established. The aim of this study was psychometric evaluation of the short version of the DSQ-40 on a Serbian male middle-age non-clinical sample. Methods. Internal consistency, factor structure and discriminant and concurrent validity of the DSQ-40 were studied in 284 high selected male professional military personnel aged 23 to 53 years (35.09 ± 7.21 years). Results. The Cronbach alpha coefficient revealed a high internal consistency for the entire scale, which confirms the compactness and high reliability of this questionnaire [Intraclass correlation coefficient (ICC) = 0.724; p
Keywords: defense mehanisms; military personnel; male; adult; surveys and questionnaires; psychological tests; serbia